The forums of Conimbriga and Aeminium: comparison and summary of the state of the art. - Alarcão, Jorge de (2017)
This paper presents the forums of the Roman cities of Conimbriga (Condeixa-a-Velha, Portugal) and Aeminium (Coimbra, Portugal), both of which date from the time of Augustus. The Aeminium forum was completely rebuilt in the time of Claudius/Nero, while the Conimbriga one was remodelled in the same period, before being demolished under the Flavians to make way for a completely new construction. This article offers a state-of-the-art comparison of the architectural models used in these two cities, based on the analysis and review of the available data, partly supplied by recent archaeological excavations. The geographic and chronological proximity of these two forums mean that it is of interest to compare their architectural design, which differ considerably in aspects such as volumetry, layout and the conceptual model used. The article discusses the proposals for the development of the Conimbriga forum and indicates an up-to-date bibliography for both public spaces, resulting, in the case of Aeminium, from a large-scale research and intervention project carried out in recent years.